Seleção de parceria e processo de governança da colaboração na inovação aberta sustentável: um estudo em projetos de P&D em parceria com o mercado para a descarbonização da agropecuária - Fragalle, Cristiane Vieira Peres (2024)
One of the challenges for Brazil and the world in the coming decades is the decarbonization of agriculture. The topic is at the frontier of scientific knowledge and depends on several actors to reach a solution. Brazil established public policy to meet the goals negotiated at COP 21 through the Low Carbon Agriculture Plan (Plan ABC+), which aims to reduce carbon emissions from the agricultural sector by 1.1 billion tons by 2030. By encouraging adoption of more sustainable agricultural and livestock practices, the plan encourages the search for innovative solutions and technologies that can contribute to reducing GHG emissions, increasing agricultural productivity and conserving natural resources, simultaneously. Embrapa, a Science, Technology and Innovation (ICT) institution, contributes to achieving the goals of the ABC+ Plan through its research into climate change. It has faced an increase in demand for partnerships for decarbonization in open innovation projects in a context where organizations have sought to adapt to new business models that meet sustainability. Academic literature points out that innovations involving sustainability can bring new challenges to the selection of partners and to the governance process of collaboration in these partnerships, since the actions are long-term, seek to generate new knowledge, there is interdependence of different actors and its objective goes beyond the economic dimension. It is a topic still under development, with few existing studies on collaboration when it takes place between organizations, something seen by authors as a “black box” of the collaboration process to generate innovation. This type of process is also new for Embrapa and previous interviews with managers of these projects pointed to the differences in this type of project and the need to better understand the collaboration selection and governance processes. The latent processes and criteria that take place in projects can help Embrapa improve the collaboration process with its R&D partners. Given this context, this research aimed to map and propose a practice guide for partner selection processes and collaboration governance in R&D projects in a sustainable open innovation model with the market and its critical success factors. To this end, five case studies were carried out on Embrapa R&D projects focusing on decarbonization. As a result, activities in the partner selection and governance stages of the collaboration process that Embrapa projects have and the gaps when compared to the theoretical model were identified. Processes and criteria were identified at the micro level of analysis, and critical success factors were identified. As a technological product, this study developed a Guide to practices for partner selection and collaboration governance processes. In doing so, it responds to both the academic and practical gaps highlighted above.